Analysis of Diagnostic Value of CTC and CTDNA in Early Lung Cancer: Early Diagnosis of Lung Cancer - Hongwei Yao,; Lixin Wen,; Ziyan Li,; Chunwei Xia, (Cellular and Molecular Biology, 2023)
This paper is the exploration and analysis of the diagnostic value of circulating tumor cells (CTC) and circulating tumor deoxyribonucleic acid (ctDNA) in early non-small cell lung cancer (NSCLC).A total of 125 NSCLC patients that hospitalized from March 2019 to December 2020 were selected, of which 64 subjects with stage I-II were listed as the early-stage group, and 61 patients with stage III-IV were classified as the intermediate-advanced group; In addition, 47 patients with benign pulmonary nodules hospitalized within same period were selected as a group of benign pulmonary nodules, and 50 healthy subjects were enrolled as a control group. The levels of CTC and ctDNA, serum tumor markers carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), cytokeratin 21-1 (CYFRA21-1) and gastrin-releasing peptide precursor (pro-GRP) were detected. The diagnostic value of CTC and ctDNA in early NSCLC patients was analyzed by ROC curve. The area under the curve of CTC count for early-stage lung cancer was 0. 949 (P=0. 000, 95%CI: 0. 918-0. 980), and ctDNA was 0. 914 (P=0. 000, 95%CI: 0. 866~0. 963). There were significant differences in CTC count and ctDNA among subjects in each group (P<0. 05). CTC count and ctDNA of the early and intermediate-advanced group were remarkably higher than those of the control group and group of benign pulmonary nodules (P<0. 05), and CTC count and ctDNA of patients in the middle-late group were critically higher than those in the early-stage group (P<0. 05). There were significant differences in serum CEA, NSE, CYFRA21-1 and pro-GRP levels among all groups (P<0. 05). The results showed that CTC and ctDNA in NSCLC patients were significantly positively correlated with CEA, NSE, CYFRA21-1 and pro-GRP (P<0. 05). Peripheral blood CTC and ctDNA levels are significantly increased in NSCLC patients. They are positively correlated with serum tumor markers CEA, NSE, CYFRA21-1 and pro-GRP levels, and are related to tumor progression. CTC and ctDNA have high value in the clinical diagnosis of early NSCLC.